2020
DOI: 10.1002/solr.202000184
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Conjugated Polymer Based on Polyethylene Backbone as Dopant‐Free Hole‐Transporting Material for Efficient and Stable Inverted Quasi‐2D Perovskite Solar Cells

Abstract: Quasi‐2D perovskites with excellent stability have been recognized as an alternative to 3D counterparts for perovskite solar cells (PSCs). Although the power conversion efficiency (PCE) of quasi‐2D PSCs has increased over 18% by the compositional controlling and solvent engineering of perovskites, fewer studies have been conducted to exploit charge transport layers and investigate their interface relationships with quasi‐2D perovskites. To achieve high efficiency and good long‐term stability for quasi‐2D PSCs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…As the dopant-free HTM, PVCz-OMeDAD- based conventional devices showed a PCE of up to 16.1%. Recently, they further synthesized another nonconjugated polymer HTM, PVCz-OMeTPA , which not only can exhibit a good hole mobility but also match energy levels with quasi-2D perovskites . What is more encouraging is that, compared to PVCz-OMeDAD and PTAA , PVCz-OMeTPA is capable of assisting the high-quality growth of quasi-2D perovskite films and therefore delivered a promising PCE of 17.2%.…”
Section: Other Types Of Dopant-free Polymer Htmsmentioning
confidence: 99%
“…As the dopant-free HTM, PVCz-OMeDAD- based conventional devices showed a PCE of up to 16.1%. Recently, they further synthesized another nonconjugated polymer HTM, PVCz-OMeTPA , which not only can exhibit a good hole mobility but also match energy levels with quasi-2D perovskites . What is more encouraging is that, compared to PVCz-OMeDAD and PTAA , PVCz-OMeTPA is capable of assisting the high-quality growth of quasi-2D perovskite films and therefore delivered a promising PCE of 17.2%.…”
Section: Other Types Of Dopant-free Polymer Htmsmentioning
confidence: 99%
“…Besides ETLs, hole-transport layers (HTLs) also play a key role in determining the performance of PSCs. For example, 2,2′,7,7′-tetrakis­( N , N -di-pmethoxyphenylamino)-9,9′-spirobifluorene (spiro-OMeTAD), first adopted by the Park group in 2012, has become the prevalent and most successful hole-transporting material (HTM) for n- i -p PSCs. However, because of its poor electron conductivity (∼6 × 10 –5 mS/cm) and hole mobility (∼2 × 10 –4 cm 2 ·V –1 ·s –1 ), the undoped spiro-OMeTAD HTL normally shows high series resistances and poor photovoltaic performances. Thus, chemically doping spiro-OMeTAD with Li-bis­(trifluoromethanesulfonyl)­imide (Li-TFSI) and 4-tertbutylpyridine ( t -TBP) becomes the main strategy to solve this issue. Unfortunately, Li-TFSI is hygroscopic, which might facilitate water ingress into the perovskite layer. , Besides, the postoxidation procedure to dope spiro-OMeTAD could also promote perovskite degradation, induce a higher electron–hole recombination ratio at perovskite/HTL interfaces, and decrease the reproducibility. , Thus, developing alternative dopant-free HTMs is necessary and highly desirable. …”
Section: Introductionmentioning
confidence: 99%
“…Although NCPEPs promise to overcome the limitations of CPs and examples exhibiting higher charge carrier mobilities than CPs have been reported, , NCPEPs are generally found to have charge carrier mobilities several orders of magnitude lower than CPs . Taking inspiration from the work of Uryu et al, who showed that highly isotactic ( m = ∼97%) poly­(2- N -carbazolylethyl acrylate) (PCzEA) had a μ h of 1.7 × 10 –5 cm 2 V –1 s –1 (being six times higher than the atactic counterpart), we have recently showed clear evidence for the correlation of stereoregularity in PCzEA and μ h .…”
mentioning
confidence: 99%
“…28 We further showed the effect of the spacer length on the μ h of NCPEPs, where we found that a six carbon alkyl spacer is the optimum flexible spacer length to achieve high μ h in isotactic NCPEPs using highly isotactic poly(Ncarbazolylalkyl acrylates) as our model system. 29 Although NCPEPs promise to overcome the limitations of CPs and examples exhibiting higher charge carrier mobilities than CPs have been reported, 30,31 NCPEPs are generally found to have charge carrier mobilities several orders of magnitude lower than CPs. 32 Taking inspiration from the work of Uryu et al, 33 who showed that highly isotactic (m = ∼97%) poly(2-Ncarbazolylethyl acrylate) (PCzEA) had a μ h of 1.7 × 10 −5 cm 2 V −1 s −1 (being six times higher than the atactic counterpart), we have recently showed clear evidence for the correlation of stereoregularity in PCzEA and μ h .…”
mentioning
confidence: 99%